Effectiveness Of A Behavioral Intervention Program For The Promotion Of Healthy Lifestyles In Caregivers Of People With Disabilities: Empirical Quantitative Research (The Review of Diabetic Studies, 2024)
Background: The research is framed in the purpose of evaluating the effectiveness of a behavioral intervention program for the promotion of healthy lifestyles among informal caregivers of people with disabilities.                                                                             Methods: Quasi-experimental study with two groups (one intervention and one control), with pre- and post-measurements. The behavioral intervention program was structured and implemented based on the six dimensions outlined in Nola Pender’s Health Promotion Model. The instrument used to assess healthy lifestyles was the HPLP-II. It was directed at informal caregivers of people with disabilities and lasted for 16 weeks. To determine the program's effectiveness, Student's t-test for independent samples and Cohen's d effect size were used to compare the intervention and control groups.                                                                                                 Results: A significant change in healthy lifestyles was observed after the implementation of the behavioral intervention program. The intervention group obtained a total average score of 80.53 on the HPLP-II instrument, compared to 50.80 in the control group. Favorable differences were also observed in the assessed dimensions for the experimental group compared to the control group: interpersonal relationships (14.37 vs. 9.90), nutrition (12.16 vs. 8.95), health responsibility (14.79 vs. 8.25), physical activity (10.79 vs. 5.29), stress management (11.11 vs. 7.65), and spirituality (17.32 vs. 10.85). All reported differences were statistically significant (t = 5.95; p < .001). Additionally, when comparing the experimental group before and after the intervention, the total score increased from 41.84 to 80.53, with a significant difference (t = 7.81; p < .001). The effect size was 2.54 (95% CI: 1.483–3.56), indicating a positive and substantial impact of the program on healthy lifestyles in informal caregivers.Conclusions: The behavioral intervention program proved effective in fostering the adoption of healthy lifestyles in the target population, with significant improvements in the areas of physical activity, healthy eating, interpersonal relationships, health responsibility, stress management, and spirituality.